STANDARISASI LAPORAN KEUANGAN PADA MADRASAH IBTIDAIYAH BAITI JANNATI - Satria Darma (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Educational foundations are non-profit institutions that also require financial reports, where these reports can be used as a basis for decision making. The problem faced by the Baiti Jannati Sunggal Education Foundation is that reports and financial records are still not systemized manually. Therefore, as one of the responsibilities of the Tridharma of Higher Education, the author tries to make improvements to the problems encountered by using standardization of financial statements and it is hoped that financial reports will be of higher quality. In solving the problem, the stages are carried out systematically, first identifying the problem, second designing an application system for financial reporting, when implementing the system, and finally conducting an evaluation. The results obtained from these activities were designed and made a financial reporting application for the Baiti Jannati Sunggal Education Foundation. With this, financial reporting becomes reliable and timely so that it has an impact on accuracy and speed in making decisions and making financial reports effective and efficient.